Strategi Guru Pendidikan Agama Islam dalam Mengembangkan Sifat Jujur dan Tanggung Jawab pada Siswa Sekolah Dasar - Fetria Permata Sari; Pino Saputra (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Islamic Religious Education (PAI) in elementary schools not only focuses on the development of cognitive aspects, but also plays an important role in the formation of students' attitudes, morals, and characters. The values of honesty and responsibility are the main foundations that must be instilled early on, because they form noble morals, integrity, and readiness to face life's challenges. This study aims to examine PAI teachers' strategies in fostering and internalizing the values of honesty and responsibility in elementary school students. The research method uses a literature study by reviewing literature in the form of books, articles, and previous research results. The results of the study showed several effective strategies, including: providing role models, getting students used to behaving honestly and disciplined, giving advice through the exemplary story of the Prophet Muhammad, implementing contextual learning that links religious values with real life, giving simple responsibilities to students, and carrying out character-based evaluations that emphasize attitudinal aspects in addition to academics. PAI teachers have a dual role as moral role models, motivators, and facilitators who encourage students to practice the values of honesty and responsibility through intra- and extracurricular activities. This study concludes that consistent, integrated, and sustainable strategies can foster honest, responsible, and noble personalities of students, so that a smart, moral, and spiritual generation is formed.